2021
DOI: 10.3390/diagnostics11081369
|View full text |Cite
|
Sign up to set email alerts
|

Placental Types and Effective Perinatal Management of Vasa Previa: Lessons from 55 Cases in a Single Institution

Abstract: Background: We aimed to identify clinical characteristics and outcomes for each placental type of vasa previa (VP). Methods: Placental types of vasa previa were defined as follows: Type 1, vasa previa with velamentous cord insertion and non-type 1, vasa previa with a multilobed or succenturiate placenta and vasa previa with vessels branching out from the placental surface and returning to the placental cotyledons. Results: A total of 55 cases of vasa previa were included in this study, with 35 cases of type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Figure 1 shows the selection scheme used in this study. First, 1364 studies were identified, and 20 studies met the study criteria for descriptive analysis [ 14 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Two studies reported by Suzuki et al [ 36 , 37 ] used overlapped data (due to overlapping study periods); however, the outcome of interest was different in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1 shows the selection scheme used in this study. First, 1364 studies were identified, and 20 studies met the study criteria for descriptive analysis [ 14 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Two studies reported by Suzuki et al [ 36 , 37 ] used overlapped data (due to overlapping study periods); however, the outcome of interest was different in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the study type ( n = 20), all studies were retrospective in nature, 14 were original articles, 4 were case series, and 2 were case reports. Of these ( n = 20), the published years were between 1998 and 2022, and all studies were retrospective [ 14 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. No prospective studies or randomized controlled trials have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations